Investigating How “Good” Characteristics’ Presence are Related with Questions’ Performance - Souza, Cleyton; Remígio, José; Aragão, Franck; Costa, Evandro; Fechine, Joseana (BRACIS, 2016)
Social query is the practice of sharing questions through collaborative environments. In order to receive help, askers usually broadcast their requests to the entire community. However, the prerequisite to receive help is to have the problem noticed by someone who is able and available to answer. Previous works have identified a correlation between the characteristics of the questions and the outcome of receiving or not an answer. These findings suggest that there are some characteristics that are more likely to attract the helpers´ attention. Our proposal is to analyze the CQA history to identify how these so-called “good” characteristics affect the performance of shared questions. Our results suggest that: (1) answered questions present more of these “good” characteristics than unanswered ones; (2) the more “good” characteristics are present in a question, the more people it attracts; (3) the more people are attracted by a question, the faster it will be answered and more responses will be received; (4) answered questions attract more people than unanswered ones; (5) difficulty does not play a role in attracting people.